Pengaruh Kondisi Temperatur Mesophilic (35ºC) Dan Thermophilic (55ºC) Anaerob Digester Kotoran Kuda Terhadap Produksi Biogas - Darmanto, Ardyanto; Soeparman, Sudjito; Widhiyanuriawan, Denny (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Content energy of biogas is not less than energy derived from petroleum, horse manure can be used as a substrate for producing biogas. A substrate in horse manure bacteria containing framer metan which is in the animal body ruminants. Temperature is one of the important factors that affect on fermentation process. The aim of study was to find characterization production and composition content biogas from horse manure on condition temperature mesophilic (35ºC) and thermophilic (55ºC). Both of digester are running simultaneously by fermentation process for 15 days. The results obtained from the condition that generated the biogas production of thermophilic higher than the condition of mesophilic and conditions without heating. Biogas production optimum of each digester generated on day 8 for thermophilic conditions, day 10 for mesophilic conditions and day 11 for the conditions without heating. The highest result of biogas production was in thermophilic conditions (0.1411 kg). The highest percentage of methane gas production (CH4) that produced by the thermophilic digester conditions (59.8%).Keywords: biogas, mesophilic, thermophilic, horse manure.